2006
DOI: 10.1016/j.bbrc.2006.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite induces F-actin depolymerization and blockade of myosin ATPase stimulation

Abstract: Treatment of F-actin with the peroxynitrite-releasing agent 3-morpholinosydnonimine (SIN-1) produced a dose-dependent F-actin depolymerization. This is due to released peroxynitrite because it is not produced by 'decomposed SIN-1', and it is prevented by superoxide dismutase concentrations efficiently preventing peroxynitrite formation. F-actin depolymerization has been found to be very sensitive to peroxynitrite, as exposure to fluxes as low as 50-100 nM peroxynitrite leads to nearly 50% depolymerization in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…This is in agreement with other studies that have shown that ONOO Ϫ can induce both depolymerization of F-actin and inhibition of G-actin polymerization (16,51). Since a dynamic actin cytoskeleton is a significant contributor to pressure-induced myogenic activity (13,15), production of ONOO Ϫ may have a deleterious effect on cerebrovascular resistance through disruption of VSM actin following conditions of increased oxidative stress.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with other studies that have shown that ONOO Ϫ can induce both depolymerization of F-actin and inhibition of G-actin polymerization (16,51). Since a dynamic actin cytoskeleton is a significant contributor to pressure-induced myogenic activity (13,15), production of ONOO Ϫ may have a deleterious effect on cerebrovascular resistance through disruption of VSM actin following conditions of increased oxidative stress.…”
supporting
confidence: 92%
“…ONOO Ϫ has been shown to cause depolymerization of F-actin and inhibit polymerization in vitro (4,16,51). In addition, studies in neutrophils and red blood cells showed a loss of F-actin and actin-dependent functions following exposure to ONOO Ϫ that was associated with increased NT (16,22).…”
Section: Discussionmentioning
confidence: 99%
“…As described above, an explanation can emerge by the fact that actin polymerization/depolymerization is involved in vesicles trafficking, such as Glut-4, as mentioned earlier, and decavanadate interferes with this equilibrium [6]. Additionally, decavanadate is known to induce changes in reactive oxygen species production [17], and these can by themselves affect both calcium homeostasis and actin cytoskeleton dynamics, processes that are linked to each other [45]. However, besides the impact of the interaction of decavanadate with actin, perhaps the most potent cellular target of decavanadate is mitochondria, being affected by decameric vanadate concentrations as low as 0.1 μM [18,46].…”
Section: Discussionmentioning
confidence: 89%
“…Myosin is a hexameric protein, consisting of two heavy chains (MHC) of molecular weight about 200,000 and four light chains (MLC) of about 20,000 [18]. They are cell skeleton proteins and play a role in the interaction of actin thin filament [19]. Some conventional myosins, have been implicated to play vital roles in cell adhesion and phagocytosis, producing the driving force for phagosome formation and transport during phagocytosis [20,21].…”
Section: Introductionmentioning
confidence: 99%